A Gravimetric Geoid model of Tasmania, computed using the One-dimensional Fast Fourier Transform and a Deterministically Modified Kernel - Vella, J.; Featherstone, Will (Institution of Surveyors, Australia, 1999)
A new gravimetric estimate of the separation between the GRS80 ellipsoid and the geoid over Tasmania and surrounding seas has been made. The geoid model utilised a combination of the EGM96 global geopotential model, the 1992 release of the Australian gravity database, and a nine-second digital elevation model. The computational technique used was the one-dimensional fast Fourier transform (1D-FFT), which has been refined so as to include deterministically modified Stokes integration kernels. Comparisons were made among Global Positioning System heights, optical levelling on the Australian Height Datum (Tasmania) and several gravimetric geoid solutions at 14 points. This showed that the Vanicek and Kleusberg (1987) modification for a degree 20 spheroid and cap radius of 15 gave the smallest standard deviation of 186mm, which is a slight improvement upon the 232mm achieved when using AUSGEOID93.